Measurement and analysis of financial liberalization in Iraq - العبدلي سعد عبد نجم; فاضل حميد طالب (Journal of Economics and Administrative Sciences, 2018)
Abstract : In light of the trend of the countries of the world to adopt the policy t the overall stability. In this direction, competition is a condition of efficiency and competition can not be achieved unless the restrictions on The entry of new banks and financial institutions to the market, including foreign banks, as well as changing legislation and licensing regulations to ensure this. This study is coof financial openness, many countries have tended to emphasize the reforms in the financial and banking sector in order to raise its efficiency in order to supporncerned with the measurement and analysis of indicators of financial liberalization in Iraq for the period (2015-1990) using the FLI method. This indicator shows the degree of financial liberalization at that time. The use of this indicator is useful in monitoring the pace of liberalization and assessing the impact of fiscal liberalization on various aspects of the economy. This study also includes partial liberalization measures in the index. The study focused on four key variables of fiscal liberalization in Iraq: the liberalization of the interest rate; the reduction of the legal reserve; the free access of foreign banks to Iraq; the cancellation of credit controls during the study period; State-owned banks. The financial liberalization process in Iraq began in 2004, following the issuance of the new law of the Central Bank of Iraq No. 94 of 2004. Since then, the financial liberalization measures have been implemented to expand and deepen the financial system in order to increase competition and improve the efficiency of the financial sector and maintain the stability of the Iraqi financial system. All these policy instruments are expected to complement each other in achieving the overall objectives of competition and efficiency, the sound functioning of the financial system and capital markets, and stabilization of the financial sector in Iraq. The FLI shows that the financial liberalization process accelerated in Iraq during For the period from 2004 to 2015.